2021
DOI: 10.1088/1361-6463/ac2065
|View full text |Cite
|
Sign up to set email alerts
|

Discrete wavelengths observed in electroluminescence originating from Al1/2Ga1/2N and Al1/3Ga2/3N created in nonflat AlGaN quantum wells

Abstract: When nonflat Al x Ga1−x N quantum wells (QWs) for producing 285 nm light emitting diodes (LEDs) were fabricated on n-AlGaN on AlN templates with dense macrosteps on c(0001) sapphire substrates with a 1.0° miscut relative to the m[1–100] axis, composite electroluminescence (EL) spectra from both inclined and terrace zones in Al x Ga1−x N QWs (x∼ 1/3) were generated owing to compositional and thickness modulations. The shoulder or main peaks in composite EL spectra tended to locate at fixed discrete wavelengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Previous studies on the ordered structure of Al 1/2 Ga 1/2 N using FPCs used small calculation cell sizes to reduce computational cost [12,26,27]. This limitation resulted to significant differences between theoretical simulations and experimental results obtained by TEM, XRD, SAED, and EL [15][16][17][18][19][20][21][22][23][24][25][32][33][34].…”
Section: Mathematical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on the ordered structure of Al 1/2 Ga 1/2 N using FPCs used small calculation cell sizes to reduce computational cost [12,26,27]. This limitation resulted to significant differences between theoretical simulations and experimental results obtained by TEM, XRD, SAED, and EL [15][16][17][18][19][20][21][22][23][24][25][32][33][34].…”
Section: Mathematical Approachmentioning
confidence: 99%
“…Our recent analytical studies on AlGaN layers with dense macrosteps revealed the generation of metastable Al n/12 Ga 1−n/12 N (n is an integer from 2 to 10) along macrostep edgelines. Results from our previous works indicated that the atomic configurations of Al n/12 Ga 1−n/12 N should have 2 or fewer monolayer (ML) configurations [31][32][33][34][35][36][37][38]. Hereafter, n ML, represents the periodicity of the structure in the c[0001] direction, where n is the number of atomic layers in a unit cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ur recent studies on the compositional modulation in nonflat Al x Ga 1−x N (x ∼ 0.7, 0.63, 0.55, and 0.43) layers and Al x Ga 1−x N (x ∼ 0.2) quantum wells (QWs) revealed that metastable Al n/12 Ga 1−n/12 N (n: integer = 2-9) was generated in the Al-rich and Ga-rich zones. [1][2][3][4][5] Photoluminescence (PL) also indicated Al 9/12 Ga 3/12 N and Al 10/12 Ga 2/12 N in a nonflat Al 0.81 Ga 0.19 N on a 0.4°-miscut AlN substrate. 6) Furthermore, cathodoluminescence (CL) with scanning electron microscopy (SEM) from nonflat AlGaN layers (>1 μm) on the AlN by other research groups well agreed with Al n/12 Ga 1−n/12 N metastability (n: integer).…”
mentioning
confidence: 99%
“…A comparable accuracy could be expanded to x Al = n/12 (n = 2-10). 4,5) Note that this small deviation is considered to be possible when analyzing metastable AlGaN compositions, because metastability might restrict luminescence centers by reducing compositional fluctuations. The NBE wavelength interval for Δx Al = 1/24 is ∼6-7 nm, indicating the possibility of point use of CL for detecting Al (2m+1)/24 Ga 1−(2m+1)/24 N. Indeed, a 1% difference in x Al is the criterion, and the reproducibility of signals will be discussed.…”
mentioning
confidence: 99%